Norms of Cooperation in a Game of Partnership - LANDI, Massimiliano (Institutional Knowledge at Singapore Management University, 2001)
We study a model of partnership with costly commitment in an evolutionary game-theoretic framework. We introduce various types of cooperative players with different degrees of strategic sophistication. We find that a necessary condition for cooperation at the social equilibrium is that the probability of a high opportunity value falls below a certain critical threshold. Such condition, however, is not sufficient. If players are too naively cooperative, the permanence of cooperation at the equilibrium is put at risk because naive cooperation entails playing inefficient responses to other equilibrium strategies. As a consequence, naive cooperation will be present at the equilibrium selected by the social dynamics only under somewhat special conditions. If cooperators are more flexible, in that they remain in the partnership only if mated to a first stage cooperator and only in lack of favorable outside opportunities, cooperation is almost granted provided that it is Pareto efficient (perverse lock in cases under unfavorable initial conditions are possible). Finally, the selection of Pareto superior cooperation with certainty may be granted by a certain norm-oriented type of strategically sophisticated behavior, that we call Rawlsian altruism. [PUBLICATION ABSTRACT]